Validation of the transformer-based monocular system (Capture4D): A real-time kinematic analysis in coaching/teaching tennis - Zhao, Y.; Wang, S.; Gao, Z.; Wu, H.; Cui, Y.; Liu, Y. (Sensors, 2026)
Human motion capture is crucial for various fields, but traditional optical systems (OMC) are costly and restrictive. Monocular video-based methods offer accessibility, yet face accuracy challenges, especially in dynamic sports like tennis. This study validates Capture4D, a novel Transformer-based monocular system, for capturing a wide range of tennis strokes. We developed a universal biomechanical analysis framework (K0-K5) applicable to twelve fundamental stroke types. To demonstrate the system`s capabilities, this paper focused on a detailed validation using the tennis serve as a representative example. We conducted experiments with 9 high-level tennis players, and motion data were simultaneously captured using Capture4D (single RGB camera) and OMC Qualisys (gold standard). Accuracy was evaluated by comparing 3D joint coordinates and joint angles using Normalized Mean Per Joint Position Error (NMPJPE), RMSE, and MAE. The results demonstrated that Capture4D effectively captured the tennis player`s motion, with average NMPJPE for tennis serves ranging from 69.5 mm to 88.3 mm, within the acceptable range (70-130 mm) for coaching purposes. Compared to OMC, Capture4D demonstrated comparable joint angle trajectories, with advantages in operational convenience, cost-effectiveness, and wider applicability. It offered an approximately 50% reduction in setup time and 80% cost savings. Capture4D presents a valid and practical monocular motion capture solution for coaching tennis and other broader applications in sports. While slightly less precise than OMC, its accuracy is acceptable for many use cases in coaching and teaching. It offers significant advantages in convenience and cost, paving the way for accessible motion analysis in diverse environments like outdoor settings and multi-person scenarios, in which OMC is not possible to be used. This technology holds promise for democratizing motion capture in sports training and coaching/teaching.